PENGARUH PEMBERIAN ELASAGU SEBAGAI PUPUK ORGANIK PADA TANAMAN JAGUNG (Zea mays L.) UNTUK MENGURANGI PENGGUNAAN PUPUK NPKDI DESA ALINDAU KECAMATAN SINDUE KABUPATEN DONGGALA - Amalia Noviyanty; Sulmi Sulmi (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
Donggala is one of corn producer regencies in Central Sulawesi province supported by suitable climatic factors, regional potency and society aspect.  Since 2001, the government has promoted GemaPalagung program (Movement of Rice, Soybean and Corn Self-Reliance).  This program was evidently effective as shown by increasing in corn production, although it has yet to meet the domestic need of corn which is then lead to corn import (Purwono and Hartono, 2008). This indicates that efforts to increase corn production are still necessary (Ekowati and Nasir, 2011). One effort to increase production is by fertilization, especially by minimizing the use of chemical fertilizers (inorganic) that have a negative impact. Waste of processed sago known as elasaguis an organic material with high C/N ratio potentially to be used as an organic fertilizer through decomposition process.  This research aimed at obtaining balanced elasagu organic fertilizer application and its efficiency when use in corn plantation. A randomized block design was used with five rate applications of the elasagu fertilizer i.e. no fertilizer applied (control), 35 g NPK fertilizer applied, 0.7 kg elasagu applied,  0.35 kg ela sagu+50 g NPK fertilizer applied, and 0.7 kg ela sagu+35 g NPK fertilizer applied.  The research results showed that the 0.7 kg ela sagu+35 g NPK fertilizer treatment leads to highest in plant height, leaf number, and plant dry weight. Keywords: Corn, elasago and waste.